Asymmetry Price Transmission in the Deregulated Rice Markets in Bangladesh: Asymmetric Error Correction Model. Issue 4 (15th April 2016) - Alam, Mohammad Jahangir; McKenzie, Andrew M.; Begum, Ismat Ara; Buysse, Jeroen; Wailes, Eric J.; Van Huylenbroeck, Guido
ABSTRACT: There is a widely held belief among public consumers that rice prices are manipulated in Bangladesh. This manipulation may have led to price asymmetry in the vertical chain of Bangladesh rice markets. This paper is an attempt to investigate the existence of asymmetry between wholesale and retail rice prices in Bangladesh. Maximum likelihood estimation (MLE) based cointegration test was applied to determine long‐run equilibrium relationship. We examine whether the wholesale market dominates the retail market—in terms of price discovery and price leadership—or vice versa. Finally, we analyze whether the wholesale‐retail price relationship is asymmetric with respect to price increases and price decreases. To test the asymmetric price transmission we used the asymmetric error correction‐EG approach. Our results show that wholesale and retail prices are cointegrated, and wholesale market plays a leadership role in determining retail prices, which is in line with industrial organization theory. Our results confirm the fear and concerns of consumers about the existence of price asymmetry. [JEL Classification: Q110; Q113].